Good joy, bad joy : a novel - Brammer, Mikki (St. Martin's Press, 2026)
"From the bestselling author of The Collected Regrets of Clover comes a vibrant, heartfelt novel about friendship over the decades, self-discovery, and what it means to have a life well-lived. Break the rules. Find your joy. For over eighty years, Joy Bridport has played by the rules: she's been a devoted wife and mother, contributing to the community in her small Hudson Valley town. But her quiet existence is jolted when she learns that her best friend, Hazel, only has months left to live. Hazel has always been the more adventurous one of their duo, and she seems at peace with all that she's squeezed out of her long life. Yet Joy realizes she can't say the same. Determined to live boldly and make the most of the time that she and Hazel have left together, Joy steps outside of her comfort zone-and into a bit of trouble. But as her foray into rule-breaking escalates into committing petty crime, Joy must consider what kind of legacy she wants to leave behind, and whether there's a way for her to embrace the liberation that "Bad Joy" offers without losing all that she holds dear. Is it ever too late to become who we're meant to be? With laugh-out-loud hijnks and emotional heft, Good Joy, Bad Joy is a heartwarming and wise celebration of the choices we make, the friendships we cherish, and the lengths we go for love"-- Provided by publisher.